Heavy smoking rate trends and related factors in Korean occupational groups: analysis of KNHANES 2007–2012 data. Issue 11 (12th November 2015) - Kim, Bo-Guen; Pang, Do-Dam; Park, Young-Jun; Lee, Jong-In; Kim, Hyoung-Ryoul; Myong, Jun-Pyo; Jang, Tae-Won
Abstract : Objectives: The present study was designed to investigate the smoking and heavy smoking trends and identify possible related factors among Korean male workers from 2007 to 2012 by occupational groups. Methods: The data were derived from the fourth (2007–2009) and fifth (2010–2012) waves of the Korean National Health and Nutrition Examination Survey (KNHANES). Occupational groups were categorised into three groups, which were non-manual, manual and service and sales groups. Age-adjusted prevalence rates of smoking and heavy smoking (>20 cigarettes/day) in men aged 25–64 years were calculated. Factors associated with heavy smoking were investigated using logistic regression analyses. Results: Smoking rate in manual workers decreased gradually over time (p for trend <0.0001). Smoking rate was higher in manual than non-manual workers, but the difference reduced over time (p for trend <0.0001). Heavy smoking rate decreased from 2007 to 2012 (p for trend <0.0001). Heavy smoking rate was higher in manual than non-manual workers; however, this difference increased over time. Stress, depressive mood and long working hours (≥60 h/week) were associated with heavy smoking. Conclusions: Antismoking policy should focus on current and heavy smokers. Workplace antismoking programmes should consider working hours and stress, especially in manual workers.